Judges' Perspective on The Implementation of SEMA No. 2 of 2023 concerning The Registration of Interfaith Marriages - Syaifuddin Zuhdi; Lutfiah Firdaus (Universitas Muhammadiyah Surakarta, 2025)
This study aims to explore judges' perspectives on the Supreme Court Circular Letter (SEMA) No. 2 of 2023. It uses an empirical or non-doctrinal method, with primary data obtained through interviews with five judges selected via snowball sampling. The findings show that there are both pro and contra views among judges regarding SEMA No. 2 of 2023. Those opposed view it merely as guidance for judges, affirming their freedom to decide cases as it is not a binding rule. Meanwhile, supporters regard it as a breakthrough that provides legal certainty in the implementation of interfaith marriages. The novelty of this study lies in revealing that not all judges share the same opinion regarding a SEMA, indicating the need for more outreach among law enforcers, especially concerning interfaith marriage.